Producing different grades of chitosan oligomers - Aljbour, Nawzat D.; Beg, M. D. H.; Jolius, Gimbun (2018)
Chitosan, the second most abundant natural polymer used in the world after cellulose, it has attracted attention long time since it is a polycationic polymer and could be utilized in different applications especially in food, medical, and pharmaceutical fields. The major disadvantage of chitosan is its insolubility in water, while it is soluble in dilute acidic solutions such as hydrochloric acid and acetic acid. Low Molecular Weight Chitosan (LMWC) has superior properties compared to the High Molecular Weight Chitosan (HMWC), especially its water solubility in addition to the antibacterial and antifungal properties which will open new horizons for LMWC to different applications especially in the cosmetics, food, and pharmaceutical industries. LMWC could be produced from the native HMWC using different hydrolysis method such as acid hydrolysis, enzymatic hydrolysis, and oxidative hydrolysis using nitrous acid and hydrogen peroxide. In addition to the mechanical methods such as ultra-sonication and radiation. For the industrial scale depolymerization, the acid hydrolusis using diluted hydrochloric acid is preferred because it is considered simple and practical method and resulted in a very good yield up to approximately 85%, also the concentration of hydrochloric acid (2M) is considered less corrosive and aggressive effects compared with other methods. The produced LMWT grades were characterized by FTIR, NMR, and X-Ray Powder Diffraction. Also the molecular weight of each prepared grade was determined using the intrinsic method in addition to the lazer diffraction method, and the % degree of deacetylation was determined by the acid hydrolysis method. The obtained results of molecular weight determination showed that the prepared grades using 2M Hydrochloric acid depolymeraization are considered of narrow range of polydispersity, then by this method the major problem of the commercial chitosan, the polydispersity could be solved. On the other hand the obtained LMWC grades were fully deacetylated. In order to get grades with specific %DDA’s an acetylation reaction could be carried out using different amounts of acetic anhydride. In this work LMWC in three molecular weight ranges were prepared ( Mwt< 5000, 10000 < Mwt < 20000, and 20000 < Mwt < 50000) and for each range we prepared three different degrees of deacetylation (100%DDA, 80%DDA, & 60%DDA).